Innovative Approaches Fostering Self-Regulated Learning Technology as a Learning Environment in Higher Education Institutions in Uganda - Benjamin, Sserumaga K; Charles, Muweesi; Lawrence, Sserwadda; Agnes, Nabakiibi; Bosco, Lutamaguzi John; Vincent, Ssekitoleeko; Mugabo, Augustine; Judith, Nabateregga; Kizza, Ssali Francis (Research and Advances in Education, 2025)
The harmonization of technology into education has the aptitude to redefine the learning process as Zimmerman (2002) proposes, self-regulated learning and performance involve the processes whereby learners personally activate and sustain cognitions, affects, and behaviours that are systematically oriented towards the attainment of personal goals. Where the learner sets personal goals and creates self-oriented feedback through which they can monitor their effectiveness and values in this world through the use of self-regulated learning (SRL). The results of this study will establish strategies on how to utilize SRL using technology to enhance their learning environment as a competence. To know whether university students use digital technologies to plan, organize and facilitate their learning, the interviewing methodology was used. The results indicated that university students, even when they are frequent users of digital technology, tend not to use these technologies to regulate their learning process. To sum up, the findings of the study indicated that integrating self-regulated approaches into technology can improve students’ self-efficacy as well as their strategies for planning and using time and hence they can learn effectively and have better learning achievements.